0,1
Table of n, a(n) for n=0..74.
a(n)= (n+1)/2-(9*(-1)^n+1)/4. G.f.: -(2*x-1)*(x-2)/((1+x)*(x-1)^2). a(n)=a(n-1)+a(n-2)-a(n-3). [From R. J. Mathar, Jan 03 2009, Aug 14 2009]
lst={}; a=2; Do[a=n-a; AppendTo[lst, a], {n, 0, 6!}]; lst
Cf. A084964
Sequence in context: A253257 A127412 A304791 * A211343 A039661 A293668
Adjacent sequences: A152829 A152830 A152831 * A152833 A152834 A152835
sign
Vladimir Joseph Stephan Orlovsky, Dec 14 2008
Definition corrected by N. J. A. Sloane, Jan 11 2009
Formula adapted to offset by R. J. Mathar, Aug 14 2009
approved